Pencegahan Stunting melalui Pemberian ASI Eksklusif di Indonesia: Pendekatan Meta-Analisis: Stunting Prevention through Exclusive Breastfeeding in Indonesia: A Meta-Analysis Approach - Simbolon, Demsa; Putri, Nurlita (Amerta Nutrition, 2024)
Background: The direct cause of stunting in toddlers is nutritional intake, one of which is because babies do not receive exclusive breastfeeding for up to 6 months. Objectives: The purpose of this study is to measure the effect of exclusive breastfeeding on stunting prevention through a meta-analysis approach. Methods: This study uses a meta-analysis approach by searching for research articles from various databases such as Google Scholar, PubMed, and Science Direct. The keywords used are by the Medical Subject Heading (MeSH), namely "exclusive breastfeeding", "stunting", "infant", "exclusive breastfeeding", "linear growth disorder", and "stunted toddlers". The criteria for the article are publications from 2013 to 2021, can be downloaded in full text, using a cross-sectional and case-control study design, and effect size data is available in the form of Odds Ratio (OR). The process of submitting articles is presented in a PRISMA diagram. Data analysis using the Review Manager 5.4.1 application with a random effect analysis model. Presentation results in the form of forest plots and funnel plots. Discussions: 26 research articles are worthy of analysis, consisting of 9 from international journals and 17 from national journals. The Heterogeneity test results showed a p-value of 0.00001 and an I2 value of 85%. The results of the analysis with a random effect model were obtained from the forest plot which showed a pooled Odds Ratio of 2.90 (95% CI: 2.07-4.08), meaning that babies who did not receive exclusive breastfeeding had a 2.9 times higher risk of stunting compared to babies who received exclusive breastfeeding. These findings show a significant influence of non-exclusive breastfeeding on the incidence of stunting (p-value 0.0001 < 0.05). Conclusions: Exclusive breastfeeding can effectively prevent stunting.